Fabrication of a biomimetic piezoelectric polyvinylidene difluoride (PVDF) fibre with a metal core and its application in vibration sensors. (January 2018) - Bian, Yixiang; Liu, Rongrong
The fabrication is described of a vibration sensor based on the structure of the sensitive hair of some insects. The biomimetic hair has a metal core wrapped with a polyvinylidene difluoride (PVDF) layer. Two surface electrodes were coated on the PVDF surface of the fibre. A single SMPF (symmetric electrodes of metal core piezoelectric fibre) pasted on a matrix can be used as a vibration sensor. We propose a theoretical model describing the cantilever beam structure of the vibration sensor. The SMPF can detect both vibration amplitude and direction of the matrix. It can also detect the matrix harmonic excitation frequency and amplitude. We prepared PVDF fibres with metal cores (diameter: 230 µm) with the mould drawing method and used the surface electrodes and the metal core to polarize the PVDF layer. When the SMPF is used as a sensor, we only use the output signal of the two surface electrodes. Our experiments indicate that the SMPF can detect both vibration amplitude and direction of the matrix as well as the harmonic excitation frequency and the vibration direction. Our experimental results are consistent with the theoretical considerations.